2023
DOI: 10.1111/jebm.12555
|View full text |Cite
|
Sign up to set email alerts
|

Chinese guidelines for the rehabilitation treatment of knee osteoarthritis: An CSPMR evidence‐based practice guideline

Siyi Zhu,
Zhuo Wang,
Qiu Liang
et al.

Abstract: BackgroundKnee osteoarthritis (KOA) is the most common degenerative joint disease in China, causing a huge economic burden on patients, families, and society. Standardized KOA rehabilitation treatment is an important means to prevent and treat the disease and promote the development of high‐quality medical services. This guideline is updated on the basis of the 2016 and 2019 editions.MethodsClinical questions regarding rehabilitation assessment and treatment were selected through clinical questions screening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…The remaining two studies, from Chile and Lebanon, described the establishment of living guidelines. Among the four China-based studies, one reported the medications used to treat mild to moderate COVID-19 illness,42 one described the development of living Chinese medicine guidelines for treating COVID-19 patients,43 one covered a broad appraisal of the development of the living guidelines,37 and one looked at the development of a proposal for living, evidence-based guidelines on the integration of conventional Chinese medicine and Western medicine 39. The study from Lebanon showed how a framework for developing living recommendations for healthcare was produced, and the study from Chile emphasised the significance of thresholds for developing the living recommendations that are defined for the treatment of COVID-19 40…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two studies, from Chile and Lebanon, described the establishment of living guidelines. Among the four China-based studies, one reported the medications used to treat mild to moderate COVID-19 illness,42 one described the development of living Chinese medicine guidelines for treating COVID-19 patients,43 one covered a broad appraisal of the development of the living guidelines,37 and one looked at the development of a proposal for living, evidence-based guidelines on the integration of conventional Chinese medicine and Western medicine 39. The study from Lebanon showed how a framework for developing living recommendations for healthcare was produced, and the study from Chile emphasised the significance of thresholds for developing the living recommendations that are defined for the treatment of COVID-19 40…”
Section: Resultsmentioning
confidence: 99%